Effects of substitution of Bermuda grass hay with Trichoderma fermented rice straw on growth, blood, and rumen fluid parameters in Barbados sheep. Issue 1 (1st January 2018) - Pan, Yuan-Guang; Lin, Wei-Chih; Lo, Chaur-Tsuen; Chang, Shen-Chang; Yu, Bi; Lee, Tzu-Tai
ABSTRACT: The study was to ascertain the feasibility of using rice straw fermented by Trichoderma as ruminant roughage. Three species or three strains of Trichoderma (NTLg-Te S5-1, NTLg-Te S9-1, and Tien Chung Ca6-1) were used to inoculate hot water-sterilized rice straw. Result showed that rice straw fermented with Trichoderma NTLg-Te S5-1 had the highest cellulase and xylanase activity. Antioxidant ferulic acid content of water extract was improved after fermentation. Eighteen Barbados sheep were randomly distributed into one of three dietary groups. Ration of Bermuda hay group (BER) is 90% Bermuda hay with 10% concentrate. Unfermented rice straw (RS) group and fermented rice straw (FRS) group substituted 25% of Bermuda hay with rice straw or fermented rice straw. Dry matter intake, daily weight gain, blood analysis, and feed conversion ratio were not significantly different among groups after 4 weeks of trial. Dry matter digestibility of BER was the highest, and of FRS was significantly higher than RS. Malondialdehyde (MDA) content in serum of FRS and BER was lower than RS. These results indicated that 25% substitution of Bermuda hay with Trichoderma -fermented rice straw in the diet of Barbados sheep could increase digestibility and inhibit lipid oxidation when compared to unfermented rice straw.